Mapping Global Research Trends on Differentiated Instruction: A Bibliometric Analysis of Two Decades of Scholarship - Andriani, Yulia; Firmansyah, Firmansyah; Novianto, Anwar; Muhamad Firdaus, Fery; Wuryandani, Wuri; Rahmiati, Filda (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to map the evolution, influence, and thematic structure of global research on Differentiated Instruction (DI) published between 2005 and 2025. It examines the field’s developmental trajectory, key contributors, and emerging research directions that reflect the growing emphasis on inclusive and adaptive education. Methods: A bibliometric approach was conducted using 743 documents indexed in the Web of Science Core Collection. Analyses were performed with RStudio and VOSviewer to assess publication growth, citation patterns, co-authorship networks, and keyword co-occurrences. The study also identified thematic clusters and trend topics to trace the conceptual and methodological development of DI scholarship over two decades. Results: The findings indicate an annual growth rate of 11.77%, demonstrating that DI has developed into a dynamic and interdisciplinary research domain. The United States, Germany, and China emerged as the most influential contributors, while Teaching and Teacher Education and the International Journal of Inclusive Education were identified as leading journals. Four dominant research clusters were revealed: inclusive education, teacher professional development, technology integration, and student achievement. Novelty: This study provides the first comprehensive bibliometric mapping of DI research spanning 20 years, highlighting the shift from traditional differentiation toward digitally adaptive and equity-oriented pedagogies. The findings offer an evidence-based overview that supports the advancement of 21st-century inclusive teaching.